School Strategies in Shaping Student Discipline Character at Santi Witya Serong Lower School Pattani Thailand - Lina Tusafitriani, Natasya; Siti Fitriana; Venty (Indonesian Journal of Learning Education and Counseling, 2025)
This study aims to determine the strategies set by Sekolah Rendah Santi Wittya Serong School Pattani Thailand in forming students' disciplined character, as well as the obstacles and solutions faced in the process. The method used is descriptive qualitative with data collection through interviews with five informants, consisting of the vice principal, homeroom teacher, and three students, as well as observations in the school environment. The results show that the school implements several strategies to form students' disciplined character, such as habituating routine activities (dhuha prayer, prayer before learning begins), implementing clear rules, giving educational reprimands or punishments, and being an example from an educator. However, there are several obstacles such as low student awareness of the rules that apply in schools and lack of understanding of the rules that have been in effect. To overcome this, the school also collaborates with parents of students through regular meetings, and provides socialization regarding the importance of disciplined character in students. This study concludes that the formation of disciplined character requires collaboration between schools, students, and parents of students, as well as conducting continuous evaluation of the strategies set.